'Women's work penalty' in access to flexible working arrangements across Europe. (March 2019) - Chung, Heejung
Many assume that women and workers in female-dominated workplaces will have better access to flexible working arrangements. Some use this as justification for the low wages found in these workplaces. Yet, empirical results are mixed. I explore this question by examining workers' access to schedule control across 27 European countries, and find no discernible gender differences in access to schedule control when individual and company-level characteristics are taken into account. However, working in female-dominated jobs and/or sectors significantly reduces access to schedule control for both men and women. This 'women's work penalty' in female-dominated sectors varies across Europe but nowhere was the access better compared to sectors where both genders are equally represented. This raises concerns regarding the lack of favourable working conditions, in addition to low pay found in female-dominated workplaces.